Hypotonic MR Duodenography in Evaluation of Peryampullary Duodenal Diverticula - Getsov, Plamen; Vladimirov, Borislav (International Journal For Research In Health Sciences And Nursing, 2017)
Diverticulosis of the gastrointestinal tract is considered a disease of the modern world. This fact is explained by reduced fiber content of food in daily diet and aging. 80% of primary duodenal diverticula arising in retroperitoneal space medial to the second part of the duodenum at a distance of 20 mm from the ampulla of Vater. This group is known as periampulary diverticula (PAD). Proper display of the duodenal lumen and disease processes in its wall depends on its optimal distension and relaxation. Modern cross sectional imaging techniques, including computed tomography (CT) and magnetic resonance (MRI) have several shortcomings in the depiction of the duodenum because of its more complex anatomic structure, leading to its suboptimal imaging. To correct these deficiencies it is required use of drugs affecting peristaltic activity of smooth muscle in combination with oral contrast agent and distension of intestinal lumen.